1984
DOI: 10.2170/jjphysiol.34.883
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac output determined by the CO2 rebreathing method with correction of lung-bag volume shrinkage.

Abstract: The purpose of this study was to elucidate the effect of lungbag volume shrinkage on P'vco2 estimated by the C02 rebreathing method and to correct its effect in calculation of cardiac output. The P'vco2 was extrapolated with the linear relationship between dPAco2 Jdt and PAc o 2 during rebreathing. The P'vc o 2 was higher than real mixed P002 by 0.82 mmHg at rest, by 1.35 mmHg at 50W, 1.57 mmHg at 100W, and 3.06 mmHg at 150W considering the effect of lung-bag volume shrinkage detected by argon concentration. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…And, there are a number of controversial points in connection with the theory of the equilibrium attamed. 15)- 19) It has been reported that, in the equilibrium method , because a high CO2 content is inhaled into the alveoli , discharge of CO2 from mixed venous blood is impeded and partial pressure exchange between the alveoli and arterial blood increases. Jones et al20) perform downstream corrections to counter this influence, though the theoretical basis for their revisions is in Jpn.…”
Section: Discussionmentioning
confidence: 99%
“…And, there are a number of controversial points in connection with the theory of the equilibrium attamed. 15)- 19) It has been reported that, in the equilibrium method , because a high CO2 content is inhaled into the alveoli , discharge of CO2 from mixed venous blood is impeded and partial pressure exchange between the alveoli and arterial blood increases. Jones et al20) perform downstream corrections to counter this influence, though the theoretical basis for their revisions is in Jpn.…”
Section: Discussionmentioning
confidence: 99%